LncRNA PMS2L2 is downregulated in sepsis-induce acute kidney injury and inhibits LPS-induced apoptosis of podocytes - Fengxiang Zhang; Xigang Luo; Yi Wang; Lingling Ma; Dapeng Sun (Karger Publishers, 2023)
Background: Long non-coding RNA (lncRNA) PMS2L2 can inhibit inflammation induced by LPS, while LPS plays an important role in sepsis, indicating the possible involvement of PMS2L2 in sepsis. Methods: Expressions of miR-21 and PMS2L2 in patients with acute kidney injury (AKI), sepsis patients without AKI induced and healthy controls was determined by performing RT-qPCR. Overexpression assay was performed to explore the crosstalk between miR-21 and PMS2L2. Methylation-specific PCR (MSP) was performed to explore the role of PMS2L2 in regulating the methylation of miR-21 gene. The role of miR-21 and PMS2L2 in the apoptosis of CIHP-1 cells induced by LPS was assessed by cell apoptosis assay. Results: PMS2L2 was downregulated in AKI patients induced by sepsis compared to sepsis patients without AKI and healthy controls. MiR-21 was also downregulated in AKI induced by sepsis and positively correlated with PMS2L2. In addition, in cells of human podocyte cell line (CIHP-1), overexpression of PMS2L2 promoted the expression of miR-21, while miR-21 did not affect the expression of PMS2L2. MSP analysis showed that overexpression of PMS2L2 decreased methylation of miR-21. LPS treatment downregulated PMS2L2 and miR-21 in a time-dependent manner. PMS2L2 and miR-21 decreased the apoptosis of CIHP-1 cells induced by LPS, and co-overexpression of PMS2L2 and miR-21 showed stronger inhibitory effect. Conclusions: PMS2L2 is downregulated in AKI induced by sepsis and inhibits LPS-induced apoptosis of podocytes.